Geological Problems in Underground Oil Deposits - Turdiyev Farid Razzok ugli; Urinov Fazliddin Najmiddin ugli (Scientific Trends, 2024)
The most important advantage of systems is the continuous unfolding of systematic areas, that is, areas that we choose and are the product of our perception.The existence and development processes of animate and inanimate nature take place in the same direction. Human evolution is expressed in its transformation from primitive forms to aquatic animals, adaptation to living on land, crawling reptiles, and finally organisms with different levels of development. The crystallization of granite reflects the evolution of the origin and development of the Earth. It's roughly like the difference in longevity between a checkerboard game, a multiplication table, and a chess game on asphalt.